2021
DOI: 10.1155/2021/2027421
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Inflammatory Cytokines between Spinal and General Anesthesia following Changes in Ischemic Reperfusion due to Tourniquet during Lower Limb Surgery

Abstract: Background and Objective. The injuries caused by reperfusion of blood can lead to significant adverse effects after surgery. This study aimed to compare the effects of spinal and general anesthesia on inflammatory cytokines following changes in ischemic reperfusion due to tourniquet in lower limb surgeries. Methods. In this randomized controlled clinical trial, 34 patients with lower limb surgery admitted at the orthopedic ward of Imam Reza Hospital, Birjand, Iran, were selected by the available sampling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Liu et al [21] found that postoperative peroxidase (POD) patients signi cantly increased CRP and IL-6. Ganjifard M et al [22] found that in ammatory response was increased after use of tourniquet. Our results are consistent with previous studies, it shous that early systemic in ammatory response maybe the key to the occurrence of POD, and the increased incidence of POD after tourniquet use may be related to the aggravation of systemic in ammatory response caused by tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [21] found that postoperative peroxidase (POD) patients signi cantly increased CRP and IL-6. Ganjifard M et al [22] found that in ammatory response was increased after use of tourniquet. Our results are consistent with previous studies, it shous that early systemic in ammatory response maybe the key to the occurrence of POD, and the increased incidence of POD after tourniquet use may be related to the aggravation of systemic in ammatory response caused by tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 23 ] found that POD patients had significantly increased CRP and IL-6. Ganjifard M et al [ 24 ] found that the inflammatory response was increased after the use of tourniquets. Our results are consistent with previous studies, suggesting that an early systemic inflammatory response may be the key to the occurrence of POD.…”
Section: Discussionmentioning
confidence: 99%